Analisis Daya Saing Ekspor Teh Indonesia di Pasar Internasional - Cahyaningsih, Silvia; Wulandari, Siti Abir; Kemala, Nida (Jurnal MeA (Media Agribisnis), 2025)
The purpose of this research is to find out the description of strong or weak competitiveness. Indonesia’s tea exports with several other countries in the international market. The research was carried out in Indonesia, with the selection of locations because Indonesia is one of the countries that is competent in the international market. The research method used is a literature study method to describe the compatitiveness of Indonesian tea exports in the international market and the sampling technique is by means of a purposive sampling technique. Ranked fourth with an Indonesian RCA value of 0,99. In terms of competitive advantage (ECI) tea year. 2021, Indonesia is ranked fourth with an ECI value 0,88 Indonesian tea trade spesialization (ISP) in 2021 with an ISP value of 0,59 which is fourth in the Internasional market